Формування собівартості промислової продукції на основі системи гоал-костинг - Чернишенко, Олена Іванівна (Український державний університет залізничного транспорту, 2025)
У статті розглянуто концепцію та методологічні підходи до розробки системи формування собівартості продукції промислових підприємств на основі методу гоал-костинг (goal-costing). Актуальність дослідження зумовлена необхідністю підвищення ефективності управління витратами у контексті зростаючої конкуренції та необхідності адаптації до вимог ринку. Проаналізовано існуючі підходи до калькулювання собівартості та виявлено їхні обмеження в умовах сучасного виробництва. Запропоновано структурну модель системи формування цільової собівартості, яка враховує стратегічні цілі підприємства, потреби споживачів та ринкову ситуацію Розроблено алгоритм формування цільової собівартості з урахуванням ключових факторів впливу, таких як інноваційність продукції, гнучкість виробництва та інтеграція з інформаційними системами управління. Представлені результати можуть бути використані для оптимізації цінової політики, підвищення рентабельності та стратегічного планування діяльності промислових підприємств.

The article considers the concept and methodological approaches to the development of a system for forming the cost of production of industrial enterprises based on the goal-costing method. The relevance of the study is due to the need to increase the efficiency of cost management in the context of growing competition and the need to adapt to market requirements. The existing approaches to cost calculation are analyzed and their limitations in the conditions of modern production are identified. A structural model of the system of formation of the target cost, which takes into account the strategic goals of the enterprise, the needs of consumers and the market situation, is proposed. An algorithm for the formation of the target cost has been developed, taking into account key factors of influence, such as product innovation, production flexibility and integration with management information systems. It is determined that the goal costing method has the greatest potential for integration into strategic and innovative production management. A structural and functional model of the cost formation system, which is based on the principles of target planning, cost control and reverse engineering, is proposed. This model takes into account external market constraints, profit targets, internal production resources, and optimization opportunities. An algorithm for the formation of the target cost of production has been developed, which provides for the step-by-step establishmentof marginal parameters of costs, control of implementation at different stages of the product life cycle and the use of digital accounting and analysis tools. The practical feasibility of implementing the developed system to increase the flexibility of management decisions, form a competitive price, minimize the risks of exceeding costs and ensure sustainable financial development of the enterprise has been proved. The presented results can be used to optimize pricing policy, increase profitability andstrategic planning of industrial enterprises.
Formation of cost cost of industrial products based on the goal-costing system
Keywords: гоал-костинг; цільова собівартість; управління витратами; промислове підприємство; калькулювання; goal-costing; target cost; cost management; industrial enterprise; costing